KONSTRUKSI SOSIAL PERNIKAHAN ADAT SUKU OSING DESA KEMIREN, KECAMATAN GLAGAH, KABUPATEN BANYUWANGI - Ningwulansari, Ria Agnes; Zuryani, Nazrina; Krisna Aditya, I.G.N Agung (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
ABSTRACT This research focuses on the social construction of the Osing tribe Banyuwangi in maintaining traditional marriages. The background of this research is a traditional marriage is a sacred ceremony that contains culture, grandeur, beauty, and uniqueness. This qualitative exploratory study aims to dig deeper into the efforts of the Osing tribe in Banyuwangi to maintain and preserve Indigenous marriages. The theory used in this study is the theory of social construction from Peter L. Berger and Thomas Luckman. Forms stages of externalization, objectivation, and internalization. Externalizing the form of adaptation, Objectivation in the form of interaction, and Internalization in the form of socialization. Keywords:Osing Tribe, Externalization, Objectivation, Internalization